Pengaruh Pengembangan Karir dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan pada PT. Upods Karya Indonesia Jakarta - Yolanda Safitri; Isnurrini Hidayat Susilowati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
PT Upods Karya Indonesia is a vape manufacturer in Indonesia whose mission is to provide smokers with the opportunity to enjoy the benefits of vaping as a low-risk tobacco delivery device. This study aims to see the effect of career development and work motivation on employee job satisfaction partially and simultaneously. This study uses quantitative research methods. The sampling method uses Saturated Sampling. The sample used in the study was 62 respondents. Data collection metods in research are observation, interview, and literature study methods. The data used in this study is primary data which is data obtained directly from respondents by distributing questionnaires. The results of the T test show that the Career Development variable has a positive and significant effect on Employee Job Satisfaction. And Work Motivation Variables have a positive and significant effect on Job Satisfaction. The results of the F Test show that the Career Development and Work Motivation variables have a positive and significant effect on Employee Job Satisfaction at PT Upods Karya Indonesia.